Students‘ attitudes towards verbal peer bullying in the digital environment - Kostic, Jelena Ž (Sociološki pregled, 2022)
This paper presents the results of the survey of fourth-grader to eight-grade students in primary schools in the Republic of Serbia on the attitude towards verbal peer bullying in the digital environment. Communication via the internet and mobile phones was quite prevalent during the state of emergency and online classes. Therefore, during the research, the period immediately after the last cycle of online teaching from April to June 2021, was targeted. The assumptions we started from in our research are based on some previous research. Therefore, in the first and second part of the paper we refer to the research results and conclusions of other authors. The third part of the paper analyzes the results of our research conducted in 2021 on the basis of an anonymous survey. In this way, we tried to give recommendations for improving the prevention of verbal peer bullying in the digital environment among students from the fourth to the eight grade of primary school.